Early nutrition, growth and cognitive development of infants from birth to 2 years in Malaysia: a study protocol - Nurliyana, Abdul Razak; Mohd Shariff, Zalilah; Mohd Taib, Mohd Nasir; Wan, Ying Gan; Kit, Aun Tan (2016)
Background: The first 2 years of life is a critical period of rapid growth and brain development. During this period, nutrition and environmental factors play important roles in growth and cognitive development of a child. This report describes the study protocol of early nutrition, growth and cognitive development of infants from birth to 2 years of age.